Anomalous properties in aqueous solutions of polysaccharides - Mank, Valeriy; Melnyk, Oksana; Bakhmach, Volodymyr (My University, 2014)
The study of physicochemical properties of suspensions of polysaccharides in a wide range of mechanical stress and temperature are important in justifying the technological conditions of production of quality food.
Keywords: polysaccharides; starch; polimorphic; transformation; полісахариди; крохмаль; поліморфний; перетворення; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра експертизи харчових продуктів